O setor leptônico neutro e a violação de CP - Chaves, Tiago Leite [UNESP] (2006)
We present a review of the main experiments which have observed a deﬁcit in the solar neutrino ﬂux, leading to the establishment of the Solar Neutrino Puzzle. Also, we comment on the atmospheric neutrino anomaly. The study of these two systems suggest that a ﬂavor conversion mechanism must be a solution for both deﬁcits. This mechanism, known also as neutrino oscillation, requests that mass and mixing have to be introduced in the neutral leptonic sector. After that we have studied neutrino oscillation in vacuum and in matter. Next, in viewing of the potential importance of neutrino masses, as suggested by all neutrino oscillation data, we have studied the neutral leptonic sector describing some illustrative neutrino mass models. Finally, we have studied CP violation in neutrino oscillation. First, we deﬁne the Dirac and Majorana CP violation phases. Second, we discuss in some details the process of neutrinoless double beta decay 0'nü' 'beta beta' showing that it is the best way to provide an evidence for revealing the Dirac or Majorana neutrino character. In particular, we have shown that CP violation in neutrino oscillation is completely insensitive to that question, i.e., if neutrinos are Dirac or Majorana particles. We have also discussed the importance of the mixing parameter 'teta IND. 13' for detecting CP violation in the neutral leptonic sector. To conclude, we comment brieﬂy on both Double CHOOZ and Angra Project experiments. These experiments are aimed to measure 'teta IND. 13' improving the present limits constrained by CHOOZ